EMPLOYEE RECRUITMENT AT PT CAREFASTINDO MEDAN BRANCH: REKRUTMEN KARYAWAN PADA PT CAREFASTINDO CABANG MEDAN - Ndruru, Yofendi (LPPM UPMI, 2024)
A brief history of PT. Carefastindo, which was previously called S2 Cleaning Service. This company has developed an experienced management structure and PT Carefast has become a national cleaning service company based in Jakarta. In 2014, Carefast has developed into a national cleaning company with 7,000 employees. , 2004 clients and 8 branch offices, spread across Medan, Cikarang, Bandung, Semarang, Surabaya, Bali, Manado As a company operating in the Facility Service sector, we have committed to ensure our clients can focus on their own business and achieve their business efficiency by providing & facilitating integrated services for all our clients.